KARAKTERISTIK CAIRAN SEREBROSPINAL PADA KEGANASAN HEMATOLOGI - Yunni Diansari,* Tiara Aninditha,** Rini Andriani*** (NEURONA, 2017)
INTRODUCTION HEMATOLOGIC MALIGNANCIES SUCH AS LEUKEMIA AND LYMPHOMA DEMONSTRATES LEPTOMENINGEAL CELL INFILTRATION MORE FREQUENTLY THAN SOLID TUMORS A SPECIAL APPROACH IN DIAGNOSIS AND MANAGEMENT IS NECESSARY INCLUDING ANALYSIS OF CEREBROSPINAL FLUID CSF OBTAINED FROM LUMBAR PUNCTURE LP THE OBTAINED CSF MAY HAVE PROPERTIES SIMILAR TO CNS INFLAMMATION THERE HAS BEEN NO SPECIFIC RESEARCH DESCRIBING THE CSF CHARACTERISTICS OF HEMATOLOGIC MALIGNANCY IN INDONESIA NONETHELESS IT IS ESSENTIAL BECAUSE IF FOUND THE SUBSEQUENT MANAGEMENT OF THE PATIENT WILL BE QUITE DISTINCT